Analisis Kesulitan Pelajar Indonesia dalam Gramatika Bahasa Jepang - Andi Irma Sarjani; C. Dewi Hartati (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Japanese as one of the foreign languages ​​that is widely studied in Indonesia, is not an easy language to learn, because Japanese is unique and has vocabulary and grammatical constructions that are not the same as other languages. Therefore, many Indonesian learners whoa are studying Japanese, faces difficulties both in terms of very diverse kanji characters and in learning Japanese grammar itself. This study aims to clearly identify the problem points in studying Japanese grammar, especially for Indonesian students who are studying Japanese. In this study, a statistical method was used, namely a questionnaire with Indonesian student respondents who had mastered Japanese quite well. This questionnaire on Japanese grammar takes the object of Indonesian students who are learning Japanese who are continuing their studies at several universities in Tokyo, Japan. The conclusion of the research is that 60％ respondents said that the biggest problem for Indonesian students in Japanese grammar is the passive voice.